2002
DOI: 10.1164/rccm.2112074
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplementation and Lung Functions among Children with Asthma Exposed to High Levels of Air Pollutants

Abstract: To evaluate whether acute effects of ozone, nitrogen dioxide, and particulates with mass median diameter less than 10 micro m could be attenuated by antioxidant vitamin supplementation, we conducted a randomized trial using a double-blinded design. Children with asthma (n = 158) who were residents of Mexico City were randomly given a daily supplement of vitamins (50 mg/day of vitamin E and 250 mg/day of vitamin C) or a placebo and were followed from October 1998 to April 2000. Pulmonary function tests were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
3
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(206 citation statements)
references
References 33 publications
5
191
3
7
Order By: Relevance
“…Shortterm randomised supplementation trials suggest that antioxidant vitamins and n-3 polyunsaturated fatty acids might protect against the acute effect of these pollutants, particularly in vulnerable subgroups [80,96,106]. However, the evidence is still limited because of the small sample size in most studies and the lack of comprehensive assessment of baseline nutritional status and oxidative stress response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortterm randomised supplementation trials suggest that antioxidant vitamins and n-3 polyunsaturated fatty acids might protect against the acute effect of these pollutants, particularly in vulnerable subgroups [80,96,106]. However, the evidence is still limited because of the small sample size in most studies and the lack of comprehensive assessment of baseline nutritional status and oxidative stress response.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, healthy adults were randomised to receive vitamin C (650 mg), vitamin E (75 mg) and b-carotene (15 mg) for several weeks [80,[93][94][95]. More recently, a study of asthmatic children exposed to high levels of air pollutants in Mexico City also suggested that supplementation with vitamin C (250 mg?day -1 ) and vitamin E (50 mg?day -1 ) had a modulating effect on acute lung function changes [96]. The positive effect of antioxidant supplementation was mostly found in children genetically susceptible to the effects of oxidants (glutathione S-transferases (GST)M1 null genotypes) [97].…”
Section: Antioxidant Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…The residence of each child who participated in this study was located using a map and the closest monitoring station was assigned to that residence. 26 The ozone exposure data were collected for the year prior to the time of entry into the study. The parameter we used was the annual average of the daily maximum 8 h averages.…”
Section: Study Design and Subject Enrollmentmentioning
confidence: 99%
“…Additional research is discovering that vitamin C can be helpful in preventing asthma [1]. Protecting against cancer, [2] and supporting healthy blood sugar levels in diabetics [3].…”
Section: Introductionmentioning
confidence: 99%